Exploring Passenger Loyalty: A Perspective Through Expectancy Theory in Public Transport Usage - Zakaria, Husna; Md. Rohani, Munzilah; Ibrahim, Asmah; Ling, Felix Ngee Leh; Samsudin, Norita; Kasno, Siti Fadzilah; Jablan, Nurul Adila (Journal of Techno-Social, 2025)
The paper discusses the application of Expectancy Theory in understanding and improving passenger loyalty in public transportation systems. Expectancy Theory, originally developed by Victor Vroom in 1964, is a psychological framework that explains how individuals’ expectations influence their decision-making processes and behavior. The paper emphasizes the importance of three key components of the theory: expectancy (the belief that effort will lead to performance), instrumentality (the belief that performance will result in desired outcomes) and valence (the value placed on those outcomes). By applying Expectancy Theory to public transportation, it explores how aligning service quality with passenger expectations can enhance passenger satisfaction and loyalty. Factors such as comfort, responsiveness, facilities, safety, ticketing systems and information provision are identified as critical components of service quality that influence passenger experiences. The paper argues that public transportation providers can improve passenger loyalty by ensuring that passengers perceive a clear connection between their efforts (e.g., choosing a service) and the rewards (e.g., reliable and comfortable transportation). It concludes that a strategic approach that incorporates Expectancy Theory can lead to systematic improvements in public transportation, resulting in higher passenger satisfaction, increased loyalty, and more efficient use of resources. This approach not only benefits transportation providers but also enhances the overall passenger experience and contributes to the development of more reliable and user-friendly public transportation systems.